Psychological Dynamics of Individuals Using Shaman-Assisted Alternative Treatment: The Application of The Health Belief - Elga, Chirstin; Adiwena, Bartolomeus Yofana; Siswanto, Siswanto (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Health is a basic need for everyone. Various methods are used by individuals to treat and cure their illnesses. Many Indonesian people still use supernatural alternative medicine with the help of traditional shamans. Alternative medicine from shamans is treatment by asking a shaman to cure the disease using supernatural methods. This study aims to obtain an overview of the decision-making process of individuals who undergo supernatural alternative medicine using the help of traditional shamans regarding the theoretical framework of the health belief model. Three informants had undergone supernatural alternative medicine with the help of a shaman. The method used is a qualitative method with a phenomenological approach. Data collection techniques using the interview method. Source triangulation techniques, observer persistence, and discussions with colleagues demonstrated data validity. Data analysis was done by data reduction, presentation, conclusion, and verification with communicative validity. The results of this study indicate that the behavior of undergoing supernatural alternative medicine with the help of traditional healers is supported by several factors, such as demographic factors, perceived vulnerability, perceived severity, perceived benefits, perceived obstacles, action cues, and dissatisfaction with medical treatment. Factors of dissatisfaction with medical treatment and lack of information about the disease informants suffered became typical factors in this study. This research shows that health literacy also needs to be provided to the public so that they are more aware of healthy living behavior and have sufficient knowledge to access appropriate health services.Kesehatan merupakan kebutuhan dasar bagi semua orang. Berbagai cara dilakukan oleh individu untuk mengobati dan menyembuhkan penyakit mereka. Masih banyak masyarakat Indonesia yang menggunakan pengobatan alternatif supranatural dengan bantuan dukun. Pengobatan alternatif pada dukun adalah pengobatan dengan meminta bantuan dukun untuk menyembuhkan penyakit dengan menggunakan cara supranatural. Penelitian ini bertujuan untuk memperoleh gambaran proses pengambilan keputusan individu yang menjalani pengobatan alternatif supranatural menggunakan bantuan dukun dengan mengacu pada kerangka teori health belief model. Informan berjumlah 3 orang yang pernah menjalani pengobatan alternatif supranatural dengan bantuan dukun. Metode yang digunakan adalah metode kualitatif dengan pendekatan fenomenologi. Teknik pengumpulan data menggunakan metode wawancara. Keabsahan data ditunjukkan dengan teknik triangulasi sumber, ketekunan pengamat, dan diskusi dengan rekan sejawat. Analisis data yang dilakukan adalah reduksi data, penyajian data, penarikan kesimpulan dan verifikasi dengan validitas komunikatif. Hasil dari penelitian ini menunjukkan bahwa perilaku menjalani pengobatan alternatif supranatural dengan bantuan dukun didukung oleh beberapa faktor, seperti faktor demografis, perceived susceptibility, perceived severity, perceived benefit, perceived barriers, cues to action, ketidakpuasan terhadap pengobatan medis. Faktor ketidakpuasan terhadap pengobatan medis dan kurangnya informasi tentang penyakit yang diderita oleh informan menjadi salah satu faktor khas dalam penelitian ini. Penelitian ini menunjukkan bahwa literasi kesehatan juga perlu dilakukan kepada masyarakat agar lebih sadar akan perilaku hidup sehat dan punya pengetahuan yang cukup untuk mengakses layanan kesehatan yang sesuai.